(untitled) - Cortada, James W. (New York, 1999)
The result is an essential handbook for anyone charged with leading their firm in an economy that is global, increasingly reliant on information systems, and teeming with rapidly emerging markets--and competitors.
Keywords: Doanh nghiệp kinh doanh quốc tế,International business enterprises; Quản trị,Management